Effectiveness of the FIGO protocol for medical management of first-trimester abortion - Sepúlveda Rivera, Cintia María (2019)
Objective: To determine the effectiveness of misoprostol using the International Federation of Gynecology and Obstetrics (FIGO) 2017 protocol for medical management of first trimester abortion. Methods: A cross-sectional study was performed between March and September 2018. Seventy-six patients diagnosed with first trimester spontaneous abortion were managed following the FIGO 2017 protocol for medical management of first trimester abortion. Results: Main indications for inclusion of the 76 patients were missed abortion 57.9%, incomplete abortion 25%, and anembryonic pregnancy 17.1%. Medical induction with misoprostol followed the FIGO 2017 protocol for medical management of first trimester abortion. The most frequent side effect reported was abnormal uterine bleeding associated with pelvic pain (72.3% of patients). Complete uterine evacuation was accomplished in 98.6% of the patients. Conclusion: Misoprostol use in patients with first trimester abortion following the FIGO 2017 protocol was a safe and cost-effective therapeutic option.